Smart Tillage\ A New Revolution in Agriculture to Improve Productivity and Protect the Environment: Review - Jabbar, Hadeel Amer; Ati, Alaa Salih (American Journal of Biology and Natural Sciences, 2025)
Smart tillage is an evolving type of cultivation that uses new technologies to prepare the soil to a tee for good crop production while conserving the health of the soil and promoting sustainable farming. The process is based on the combination of all such soil sensor-based real-time data collection, global positioning systems, auto machinery, and big data analytics that finally allows for minute-to-minute adjustments in how the soil is prepared in different spots in the field. This eliminates general and very intensive soil tillage that happens with most conventional systems and allows for customizing the intensity, depth, and timing of cultivation to the specific conditions of the soil, moisture, and the crop. Such precision goes a long way in reducing soil erosion, keeping organic matter in the soil, and enhancing the activity of beneficial microbes hence, either keeping or improving fertility. Expanding the described features, smart tillage practices would contribute to such important factors as infiltration and retention of water - both components of water use efficiency, and more so in regions that have restrictions on water availability. The use of autonomous vehicles and intelligent machinery will reduce labor and fuel consumption, hence reducing the cost of production and the carbon print in farming operations. Recent studies have shown that smart tillage can improve crop yields by 5–12% and reduce fuel consumption by up to 20%, while cutting soil CO₂ emissions by approximately 30% compared to conventional tillage methods. While the benefits are proven to be true, there are still barriers that will impede the extensive implementation of smart tillage, including the high initial investment, knowledge, and skill requirements, and compatibility with existing farm management applications.